2008
DOI: 10.1203/pdr.0b013e318179957d
|View full text |Cite
|
Sign up to set email alerts
|

Novel Red Cell Indices Indicating Reduced Availability of Iron are Associated With High Erythropoietin Concentration and Low pH Level in the Venous Cord Blood of Newborns

Abstract: There is evidence that an elevated erythropoietin (EPO) concentration is associated with signs of iron deficient erythropoiesis. The aim of this study was to evaluate the iron status by means of novel cellular indices and serum iron markers and to determine whether these are associated with EPO and pH in the venous cord blood of 193 full-term newborns. There were positive correlations between EPO and the percentage of hypochromic red blood cells (%HYPOm) and reticulocytes (%HYPOr) [r ϭ 0.45 (p Ͻ 0.001) and r ϭ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This has also been proposed in earlier studies in which only severe maternal iron‐deficiency anemia has been related to iron deficiency of the newborn (47, 48). However, subtle signs of iron‐deficient erythropoiesis have also been related to impaired oxygen‐carrying capacity (EPO and pH), supporting the clinical significance of iron‐deficient erythropoiesis even in the absence of anemia (38, 39). Hence, it would be beneficial to assess maternal iron status in order to ensure the overall sufficiency of iron for pregnant women and fetuses, and also potentially select those mothers who would benefit from iron supplementation.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This has also been proposed in earlier studies in which only severe maternal iron‐deficiency anemia has been related to iron deficiency of the newborn (47, 48). However, subtle signs of iron‐deficient erythropoiesis have also been related to impaired oxygen‐carrying capacity (EPO and pH), supporting the clinical significance of iron‐deficient erythropoiesis even in the absence of anemia (38, 39). Hence, it would be beneficial to assess maternal iron status in order to ensure the overall sufficiency of iron for pregnant women and fetuses, and also potentially select those mothers who would benefit from iron supplementation.…”
Section: Discussionmentioning
confidence: 53%
“…The ethics committee of the Pohjois‐Savo Health Care District approved the study. Detailed descriptions of the enrolling protocol and laboratory measurements are given in earlier publications (22), 37–39. The pregnant women, who had been admitted to the hospital for delivery in the Pohjois‐Savo Health Care district, were collected during a 10‐month period from July 2004 to April 2005.…”
Section: Methodsmentioning
confidence: 99%
“…Sweet et al [25,26] as well as Ervasti et al [27,28,29] used the same study population for more than one publication, and just one of each of these publications [25,27] was listed in the tables. We contacted 22 of 30 corresponding authors of the original publications cited herein.…”
Section: Resultsmentioning
confidence: 99%
“…The positive association between EPO and Hb was unexpected, because low Hb concentrations would be expected to stimulate EPO production as seen in adults (68) and neonates with severe anemia (hemolytic anemia and Rh immunization) (69,70). However, other studies in healthy term neonates also reported a lack of significant direct association between Hb and EPO, although these study cohorts included only non-anemic neonates (71,72). Erythroferrone is a newly identified Fe regulatory hormone, which is stimulated by EPO to reduce hepcidin expression (60).…”
Section: Discussionmentioning
confidence: 98%